A novel stem cell associated marker identified by monoclonal antibody HESC5:3 differentiates between neoplastic lesions in follicular thyroid neoplasms. Issue 7 (9th May 2015) - Heikkilä, Annukka; Fermér, Christian; Hagström, Jaana; Louhimo, Johanna; Mäenpää, Hanna; Siironen, Päivi; Heiskanen, Ilkka; Nilsson, Olle; Arola, Johanna; Haglund, Caj
<x xml:space="preserve">Abstract</x> Follicular thyroid lesions are the bane of cytopathology. Differentiation between adenoma and carcinoma is impossible, and often these neoplasms are indistinguishable even from uninodular goitre. In other cancers as well, a theory of stem cells as the origin of cancer has been discussed in thyroid carcinogenesis. We aimed to examine a novel stem cell associated marker identified by monoclonal antibody HESC5:3 in follicular lesions in an attempt to find a marker for differential diagnosis in thyroid cytopathology. HESC5:3 was raised against and is specific for undifferentiated human embryonic stem cells. The epitope of this novel antibody is to be defined. Immunohistochemical expression of HESC5:3 was examined in clinical material comprised of follicular neoplasms (83 adenomas, 43 carcinomas) and non‐neoplastic lesions (41 goitrous, 22 hyperplastic, 23 normal tissue specimens). Staining differed significantly between neoplastic and non‐neoplastic lesions. Nuclear staining was increased in non‐neoplastic cells, whereas in neoplastic cells expression was mainly cytoplasmic. There was no difference between benign and malignant lesions, suggesting a role in early tumourigenesis. In conclusion, the HESC5:3 epitope may be of benefit as a neoplasia marker in distinguishing between uninodular goitre and neoplasia. Characterization of the epitope would increase the interest in this promising new stem cell associated marker.